Circular business model based on industrial symbiosis of microalgae cultivation for biodiesel production - Angelo, Ana Carolina Maia (2019)
Microalgae are an attractive feedstock for biodiesel production. Owning to various factors affecting microalgae growth, focus has been given on studies of the technical feasibility of microalgae cultivation with CO2 injected from industrial flue gases. However, microalgae-based biodiesel is still far from the commercial production due to various bottlenecks, which may be overcome by considering microalgae biomass production as a business opportunity when integrated with an industrial plant under the Circular Economy perspective. This study aims to develop a Circular Business Model based on industrial symbiosis of microalgae cultivation in raceway for biodiesel production, obeying the logic of value creation from waste streams from the industrial plant up to valuable final product: the biodiesel from microalgae. An integrated Business Model Canvas and Carbon Footprint analysis was applied to a hypothetical case of Brazilian cement industry using real data to assess potentialities and constraints of microalgae cultivation in Brazil in a carbon pricing context. Losses of CO2 during microalgae cultivation strongly influence the size of microalgae production facility, and consequently the area required for cultivation, as well as the economic and environmental feasibility of the business.